The Kingfisher atlas of the modern world - Adams, Simon, 1955-; Maddison, Kevin (Boston, Mass. : Kingfisher, 2007)
A collection of illustrated maps and detailed information about countries, conflicts, and people around the world from 1800 to the present.
Includes index.
7.2
3-6
Keywords: History, Modern -- Juvenile literature; Children's atlases; History, Modern; Atlases; Modern history; Atlases